Advanced applications for state estimators in smart grids : identification, detection and correction of simultaneous measurement, parameter and topology cyber-attacks - Klas, Juliana (2018)
Growing demand and concern over climate change are key drivers for renewable sources of electricity and grid modernization. Grid modernization, or the so called smart grid, not only enables renewable sources but also opens the door to new applications with far-reaching impacts such as preventing or restoring outages (self-healing capabilities), and enabling consumers to have greater control over their electricity consumption and to actively participate in the electricity market. According to the Electric Power Research Institute (EPRI), one of the biggest challenges facing smart grid deployment is related to the cyber security of the systems. The current cyber-security landscape is characterized by rapidly evolving threats and vulnerabilities that pose challenges for the reliability, security, and resilience of the electricity sector. Power system state estimators (PSSE) are critical tools for grid reliability, under a system observable scenario, they allow power flow optimization and detection of incorrect data. In this work cyber-attacks are modeled as malicious data injections on system measurements, parameters and topology. The contributions of this work are twofold. First, a model for cyber-attack as a false data injection detection and identification is presented. The presented model considers the minimization of the composed measurement error while applying the Lagrangian relaxation. The presented contribution, enables false data injection attacks detection even if this belongs to the subspace spanned by the columns of the Jacobian matrix and in network areas with low measurement redundancy Second, state-of-the-art solutions consider correction of parameters or topology when measurements are free of error. However, how may one correct measurements if parameters or topology might be simultaneously in error? To solve this problem, a relaxed model is presented and solved iteratively in a continuous manner. Once identified and detected, cyber-attacks in parameters, topology and measurements are corrected. The proposed solution is based on a Taylor series relaxed, composed normalized error (CNE) hybrid approach with Lagrange multipliers. Validation is made on the IEEE-14 and IEEE-57 bus systems. Comparative results highlight the proposed methodology’s contribution to the current state-of-the-art research on this subject. Providing mitigation, response and system recovery capabilities to the state estimator with reduced computational burden, the proposed model and methodology have strong potential to be integrated into SCADA state estimators for real-world applications.